Kritik ilmu aura oleh Hamzah Fansuri - Yusri Mohamad Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Spiritualism is part of Malay tradition since before the coming of Islam to the region especially through Hindu tantric practices. The most celebrated Malay Sufi, Hamzah Fansuri in his poems criticizes certain aspects of the spiritual traditions among Malays. One of the interesting spiritual devices that catches his attention is aura. Through analysis of the content from his poetic works, this article attempts to explain to what extent did Hamzah Fansuri appraise the science of aura.